Social support and thesis-related academic burnout among students based on maslach’s theory: A systematic review - Siswoko, Kezia Catherine; Mandagi, Ayik Mirayanti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Thesis often causes anxiety and affects mental health for final year students. It is common for students preparing a thesis to experience various psychological disorders, including stress, panic, fear, depression, and frustration due to academic burnout. Social support can affect a person's level of academic burnout and their desire to complete academic tasks, such as a thesis. Purpose: To analyse the findings from prior researches regarding the role of social support and academic burnout in final year students and determine the most dominant burnout dimension as stated in Maslach's burnout theory. Method: By identifying, screening, and selecting eligible studies from databases including Scopus and Google Scholar, the study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Result: The result revealed the role and relationship between social support and academic burnout in students completing their thesis and indicated Maslach’s three burnout dimensions (exhaustion, cynicism, and inefficacy). Conclusion: Among students who are in the process of completing their thesis, a significant negative association was identified between academic burnout and social support, with the exhaustion dimension as the dimension most often experienced by students. Keywords: Social Support, Undergraduate Students, Burnout, Maslach Dimension, Thesis.